Quy định quản lý các hoạt động hợp tác quốc tế tại Trường Đại học Quảng Bình - Trường ĐHQB, Trường ĐHQB (Lưu hành nội bộ, 2018)
Quy định quản lý các hoạt động hợp tác quốc tế tại Trường Đại học Quảng Bình